The Role of Absolute Neutrophil Count as Compared to Computed Tomography Scan in the Diagnosis of Suspected Acute Appendicitis: A Single Academic Institution Experience - Munaser S. Al-Amoodi; Abdulhaleem A. Noorwali; Saleh M. Saleh (Journal of King Abdulaziz University: Medical Sciences, 2023)
The role of absolute neutrophil count as compared to computed tomography scan, in the diagnosis of suspected acute appendicitis was determined. This is a retrospective study of 565 patients who underwent appendectomy in King Abdulaziz University Hospital from January 2010 till December 2012. The patients were divided into three groups: Clinically diagnosed group; patients who had computed tomography scan and absolute neutrophil count; and finally those who had only absolute neutrophil count. Out of 565 patients, 60 (10.6%) of them were diagnosed clinically and were found to have normal appendix. In the 290 (51.4%) patients that had computed tomography scan and absolute neutrophil count, the computed tomography scan showed 60 (21%) patients to have normal appendix, while the absolute neutrophil count showed 54 (16%) patients. The computed tomography scan accurately diagnosed 213 (73.4%) patients to have appendicitis with a sensitivity of 98.2% and, specificity of 82.2%. In comparison, the absolute neutrophil count group showed 207 (71%) patients to have appendicitis with sensitivity of 95.4% and specificity of 74%. These results correlated well with each other. Absolute neutrophil count showed a significant impact on the diagnosis of acute appendicitis confirmed by histopathological findings and supported by computed tomography scan.